Multivariate optimisation of Cr (VI), Co (III) and Cu (II) adsorption onto nanobentonite incorporated nanocellulose/chitosan aerogel using response surface methodology. (August 2020) - Shahnaz, Tasrin; Sharma, Vivek; Subbiah, Senthilmurugan; Narayanasamy, Selvaraju
Graphical abstract: Highlights: Nanobentonite impregnated Nanocellulose/Chitosan Aerogel used as an excellent alternative for removal of heavy metals. This method is simple, low-cost and enhanced the heavy metals sorption. CCD-RSM was successfully employed to optimize the process variables. Isotherm, kinetics and thermodynamics were studied. Efficiency for removal of Cr, Co and Cu was more than 98 %. Abstract: In this study, tailor made Nanobentonite incorporated Nanocellulose/Chitosan aerogel (NCNB) has been used to study its metal adsorption capacity from simulated wastewater. The aerogel was characterised with FESEM, AFM, EDX, XRD, FTIR, Raman spectroscopy and found the successful conversion to the desired adsorbent in nano dimension. This NCNB was used for optimisation of Chromium, Cobalt and Copper adsorption. Response Surface Methodology (RSM) was implemented to derive the binary correlation between various experimental parameters such as initial metal concentration, pH, adsorbent mass and temperature using Central Composite Design (CCD). The regression coefficients were evaluated which validated second order polynomial equation for the remediation of Cr, Co and Cu with NCNB. The maximum adsorption efficiencies under the optimum condition of the process parameters for Cr, Co and Cu removal were found to be 98.90, 97.45 and 99.01 % respectively. Co efficient of determination, R 2 for Cr, Co and Cu were 0.9796, 0.8973 and 0.9321 respectively. Halsey isotherm and pseudo-second-order kinetic model agreed well with the experimental data for all the three metals. Thermodynamics study showed the metal adsorption was spontaneous, endothermic and feasible in nature. These data imperatively show that use of this aerogel can be a good alternative to the expensive methods of heavy metal remediation.